Bolsa familia and food (in)security in minas gerais municipality: A study with children under seven (Revista Contexto & Saúde, 2023)
The Bolsa Família Program has been the objective of studies that show the impact of reducing extreme poverty and reducing food and nutritional insecurity (FNI). Objective: investigate the prevalence of FNI and factors associated among families with children under seven years old participating in the Bolsa Família Program, residing in a municipality in the south of the state of Minas Gerais. Methods: Quantitative cross-sectional study conducted with 145 families and 206 children under seven years old were evaluated. Results: The prevalence of FNI was 77.9%, and 15.9% of severe insecurity. The association between FNI and family income (p = 0.024), food after receiving the benefit (p = 0.006), bean consumption (p = 0.016) and snack foods (p = 0.006) were found among children of two to seven years. In addition, iron deficiency anemia was associated with the introduction of stuffed crackers (p = 0.023), packet chips (p = 0.044) and petit suisse cheese (p = 0.014) before the age of two. Conclusion: Therefore, it is expected that this research contributes to the generation of scientific evidence that will be used in decision making to improve management efficiency by redefining priorities and qualification of professionals involved in the program.
Keywords: Public Health Policy; Anemia; Food and Nutrition Security; Food and Nutrition Programs and Policies